Evaporation and condensation of pure vapor at the liquid surface in the method of lattice Boltzmann equations - Kupershtokh, Alexandr L.; Alyanov, Anton V. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2022)
The regularities of the processes of evaporation and condensation of pure steam in the method of lattice Boltzmann equations were studied. Simulation of these processes was carried out with time-stationary steam flows at the boundary of the computational domain. It is shown that quasi-stationary regimes of evaporation and condensation are realized in this case. A simple numerically efficient method was proposed for setting the steam flow on the flat boundary of the computational domain by calculating the distribution functions on the input characteristics of the lattice Boltzmann method. The calculations show that the mass flow during evaporation of a flat surface is proportional to the difference in the densities of saturated and ambient vapor at a given surface temperature that is in a good agreement with the Hertz–Knudsen law. The results of 3D and 1D modeling by the lattice Boltzmann method coincide with high accuracy. It is shown that the ratio of the density difference to the flow of matter at the phase boundary at a given temperature depends linearly on the relaxation time, both for evaporation and condensation. The effect of temperature on the intensity of evaporation and condensation flows of pure steam has been studied. The dependence of evaporation and condensation processes on the relaxation time, which determines the kinematic viscosity of the fluid, is found.